Possible effects of melatonin and omega-3 on the obesity-related hypothalamic nuclei of the electromagnetic field-exposed offspring rats: a stereological and immunohistochemical analysis - Gamze Altun; Süleyman Kaplan (Frontiers in Public Health)
AimThe main aim of the study is to qualitatively and quantitatively evaluate the neuronal changes that occur in the hypothalamic nuclei of newborn male rats related to obesity during the intrauterine period, which was exposed to electromagnetic field (EMF). It was also investigating the expressions of obesity-related neuropeptide Y (NPY) and fat mass and obesity-associated gene (FTO) in the arcuate (ARN), ventromedial (VMN), and dorsomedial nuclei (DMN). It was also aimed to examine the role of omega-3 (ω3) and melatonin (Mel) against the side effects of EMF.MethodsAdult Wistar albino pregnant female rats were randomly divided into seven groups: Cont, Sham, EMF, EMF-Mel, EMF-ω3, Mel, and ω3. While no treatment was applied to the control group, rats in the Sham group were kept in the cage system for 2 h per day for 21 days without exposure to EMF. EMF groups were exposed to 900 MHz EMF for 2 h per day during pregnancy. Mel-treated groups received 50 mg/kg/day melatonin, while ω3-treated animals were given 0.93 g/mL ω3 via intragastric gavage. Anxiety and locomotor behaviors were assessed. Oxidative stress parameters were analyzed. Stereological, immunohistochemical, and ultrastructural analyses were performed on the offspring rats’ hypothalamus.ResultsIt was seen that serum superoxide dismutase activity was significantly higher in the ω3 group compared to the other groups (p ≤ 0.01), and serum catalase activity was significantly higher in the EMF group compared to the Cont and EMF-ω3 groups (p ≤ 0.01). The number of neurons in the ARN was significantly lower in the EMF group compared to the Sham group (p ≤ 0.05). According to the open field test, the time spent in the peripheral zone in the EMF group was longer than in the Cont group (p ≤ 0.05); In the elevated plus maze test, the number of entries into the open area in the EMF group was lower than in the Cont group (p ≤ 0.01). Stronger anti-NPY immunoreactivity was observed in the EMF group.ConclusionPrenatal exposure to mobile phones may have hypothalamic effects by inducing neurodegeneration and affecting FTO and NPY expressions. The possible therapeutic effects of Mel and ω3 were not apparent.